Relationship between social media usage and body image evaluation in Malaysian youth - Khodabakhsh, Sonia (Asia Pacific Higher Learning, 2020)
Social media is one of the most influential factors that highly relates to individuals' perspectives towards many things in their lives. Besides, in recent decades, one of the important concepts among the young population is how they evaluate their body image. Therefore, this study aimed at exploring the relationship between social media usage and body image evaluation among Malaysian youth. Three hundred sixteen participants completed the online questionnaires including demographic questionnaire, Social Media Intensity, and Body Image Evaluation questionnaire. Data were analysed by Pearson Correlation method and results showed that there is a negative relationship between social media usage and body image evaluation. It means that if youth use social media excessively, they may have a low evaluation of their body image and visa versa. This relationship is a correlation and should not be considered a causal relationship. This study has implications for young people and counsellors in the field by providing awareness about the association between these two concepts.